'Pivot' and 'Rebalancing': Implications for Asia-Pacific Region. (1st January 2015) - ,; ,
Abstract : The strategic matrix of Asia-Pacific is nowadays revolving around the US pivot and rebalancing policy vis-à-vis China. The landscape is reflecting a complex state of interdependence between the US, China, and their allies. China prima facie is strengthening its economic base before robustly embarking upon modernization of its armed forces to counter-balance the US. The security environment is poised to sustain the status quo in order to avoid the detrimental effects upon their intertwined economic interests. It is argued that states are inclined to maximize their power. Chinese rise is no exception and, the rise of peer-competitor is not expected to be peaceful, testifies the past historical record. This would eventually swing the future contours of world politics toward the second phase of China-centric Cold War. Therefore, in spite of interdependence, traditionally the nation-states would tend to search for enemies thereby pushing them to accordingly recalibrate and redefine their national interests on diverse and fluid geostrategic trajectories.